PRACTICAL ANALYSIS OF GRAMMAR IN PRACTICAL LESSONS - Mamadaliyeva Burayma Sabitaliyevna (Research Focus International Scientific Journal, 2023)
Teaching grammar is becoming very debatable issue in recent days, because as Stephen Krashen (1982) said “ there is a great deal of effect on the language use of the learner and this effect is peripheral and fragile”. It is known that there are three different approaches to teaching grammar and they are teaching grammar as a product, teaching grammar as a process and the last one is teaching grammar as a skill, below we will focus on each separately.